Game-Based Learning in EFL Classrooms: Students’ Perceptions and Motivation through Zep Quiz - Diah Ayu Pertiwi; Pasca Kalisa (FOSTER: Journal of English Language Teaching, 2026)
This study investigates EFL students’ perceptions, motivation, and perceived learning effects of using Zep Quiz, a game-based learning application, in English classrooms. A qualitative descriptive approach was employed. Data was collected through a Likert-scale questionnaire distributed to 82 students and semi-structured interviews with 10 participants. Questionnaire data were analyzed descriptively using interval score interpretation to identify overall trends, while interview data were analyzed thematically to enrich and validate the questionnaire findings. The results indicate that students perceive Zep Quiz as an engaging and interactive learning tool that enhances classroom atmosphere, increases participation, and supports material review. The findings also reveal that Zep Quiz positively influences students’ motivation, focus, and enthusiasm for learning English. However, several challenges were identified, including technical issues, limited explanation of answers, and time pressure that may shift attention from understanding to speed. The main contribution of this study is to emphasize that the effectiveness of game-based learning tools depends not only on their features but also on their integration into instruction. The findings suggest that Zep Quiz is most effective when used as a supplementary learning tool accompanied by teacher guidance, explanation, and reflective discussion in EFL classrooms.